Effect of yoga-based exercise program in female patients with myofacial pain of temporomandibular disorders - Atilgan, Esra; Kurt, Hanefi; Algun, Zeliha Candan (Springer Heidelberg, 2024)
ObjectivesThe study was conducted to investigate the effect of Yoga-based exercise program on pain, range of motion (ROM), quality of sleep, depression and quality of life in female patients with myofacial pain of temporomandibular disorders (TMD).Materials and methods39 Female patients with myofacial pain of TMD were included in the study. Yoga based exercise program was performed to the first group and second group was control group. Visual Analog Scale (VAS), Neck Pain and Disability Scale (NPDS), neck and jaw ROM, Pittsburg Sleep Quality Index (PUQI), Beck Depression Inventory (BDI) and Short Form 36 (SF36) were evaluated. Evaluations were repeated before treatment and 6 weeks later.ResultsFrom the measurements, a decrease in Temporomandibular Joint (TMJ) (p = 0.005) and neck pain (p = 0.031) was found to be significant in favor of Yoga Group. It was also observed that the increase in ROM in the neck right lateral flexion (p = 0.001) in favor of Yoga Group. The sleep quality did not change. In yoga group, a decrease in depression level (p = 0,023) and increase Quality of life in parameters of physical function (p = 0.023), vital capacity (p = 0.026), emotional health (p = 0.002), mental health (p = 0.080) were found as significant, statistically.ConclusionsIt was concluded that yoga-based exercise program can be used as an alternative program in patients with myofacial pain of TMD. Further study on myofascial pain of TMD is recommended.Clinical relevanceYoga-based exercise program can be used in patients with myofascial pain due to TMD.
Keywords: Temporomandibular Disorders; Myofacial Pain; Range Of Motion; Yoga; Quality Of Lif